Good Communication Supports Pre-School Children's Ability and Its Application to Personal Hygiene Hand Washing in Kindergarten - Gea, Nurti Yunika; Agustina, Lisna; Iratnah, Iratnah (Indonesian Journal of Global Health Research, 2024)
Infectious diseases in pre-school children are prone to occur because their growth and development age is in the pre-adolescent age range or pre-school age where this age requires more space for wider movement such as schools, large fields. Hand washing is one of the knowledge that needs to be applied correctly by school-age children to maintain hand hygiene. This knowledge apart from home needs to be emphasised from the teacher at the child's school. Children's dominant activities at school make school one of the places expected to provide knowledge about proper hand hygiene. This research is a quantitative study with an analytical descriptive approach and design and method used is aquasi experiment with a pre and post without control group design approach. This study is to measure the effect of good communication on the ability of pre-school children to wash their hands. Data was collected by video recording children while washing their hands before and after the communication intervention. Bivariate data analysis using non-parametric test with Wilcoxon test because the data distribution is not normal. The results showed 40 respondents z count value of -4.465 with a p-value of (0.000) < α (0.05, this indicates that there is a significant influence between the ability of children to wash their hands before the pretest before the treatment of good communication about hand washing on the posttest after the application of good communication treatment about hand washing. It can be concluded that there is an effect of good communication on the ability of pre-school children to wash their hands.